Implementation of Merdeka Belajar-Kampus Merdeka in English Teaching and Linguistics Based on Contextual Teaching and Learning (CTL) Model at Higher Education - Manurung, Paisal; Rahayu, Sri; Subagiharti, Heni; Harahap, Dian Anggraini; Ginting, Datulina; Sambayu, Harry; Ansi, Rahma Yunita (English Teaching and Linguistics Journal (ETLiJ), 2024)
To be achievement in learning and teaching language aspects were full involvement in the selection of learning resources and materials in higher education. They were applied in everyday life. This article discussed and analysed the implementation of Merdeka Belajar-Kampus Merdeka in English teaching and linguistics based on contextual teaching and learning model in higher education. The method applied used a qualitative descriptive approach. Data’s sources included primary data: observation and interview. Then, secondary data: guidelines for Implementation of the 2021 Merdeka Belajar-Kampus Merdeka and some relevant articles. Data collection techniques were carried out using interviews, observation and documentation techniques. Techniques in determining documentation: 1) linkage of studies with reading sources, 2) engagement of studies with the results of previous research, and 3) the theory of significance and the experiences of researchers. Data analysis techniques include: 1) coding/noticing, 2) categorizing, 3) thematic analysis,4) testing and triangulation, 5) reflixivitation, 6) conclusion. The results of the study and analysis was found that there was a significant relationship between the implementation MB-KM in ETL based on CTL model, there was seem from the full involvement of students in determining learning resources in the classroom and outside the classroom, directing meaningful learning, cognitive learning in students, and developing character and creative competencies in leaning language study. These things will help students and lectures in full collaboration to build an independent competency profile in higher education to build up language proficiency.